2023
DOI: 10.1159/000530108
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Treatment Adherence in Patients with Vulvar Lichen Sclerosus

Abstract: Background: Vulvar lichen sclerosus (VLS) is a chronic, relapsing, inflammatory dermatosis that has significant impact on patients’ quality of life (QoL). While disease severity and associated QoL impact have been studied, factors associated with treatment adherence and their relation to QoL in VLS remain unexplored. Objective: To describe demographics, clinical characteristics and skin-related QoL in VLS patients, and to assess the relationship between QoL and treatment adherence. Methods: This was a cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Six questionnaires that had been applied just once in VLS research were found, the EQ-5D VAS †,5 Short Form-12 (SF-12), 5 Short-Form-36 (SF-36), 24 WHO-5 d,9 WPAI:GH, d and PHQ-9 d, 42 The subtypes QoL-dermatologic and QoL-vulvar cover the QoL-LS specific COD. Within this domain 4 questionnaires, the Skindex-29, 5,6,43 DLQI, 7,9,30,41,43 DSQL-V d , 16 and Vulvar Quality of Life Index (VQLI) 10,31,33,37,38,44 have been…”
Section: Scale Type: Qolmentioning
confidence: 99%
“…Six questionnaires that had been applied just once in VLS research were found, the EQ-5D VAS †,5 Short Form-12 (SF-12), 5 Short-Form-36 (SF-36), 24 WHO-5 d,9 WPAI:GH, d and PHQ-9 d, 42 The subtypes QoL-dermatologic and QoL-vulvar cover the QoL-LS specific COD. Within this domain 4 questionnaires, the Skindex-29, 5,6,43 DLQI, 7,9,30,41,43 DSQL-V d , 16 and Vulvar Quality of Life Index (VQLI) 10,31,33,37,38,44 have been…”
Section: Scale Type: Qolmentioning
confidence: 99%
“…Topical steroids are the recommended rst-line treatment, with 60-70% of patients achieving complete remission [5,6]. Alternatively, topical calcineurin inhibitors and complementary procedures such as photodynamic therapy have been described [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that VLS therapy can effectively reduce symptoms. However, overall patient satisfaction is moderate [5,10,11]. One-third of patients with VLS experience a signi cant reduction in health-related quality of life [10], and some women with VLS may continue to experience sexual dysfunction and less satisfying sexual activity even with treatment [12].…”
Section: Introductionmentioning
confidence: 99%
“…Topical steroids are the recommended first-line treatment, with 60–70% of patients achieving complete remission [ 5 , 6 ]. Alternatively, topical calcineurin inhibitors and complementary procedures such as photodynamic therapy have been described [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that VLS therapy can effectively reduce symptoms. However, the overall patient satisfaction is moderate [ 5 , 10 , 11 ]. One-third of patients with VLS experience a significant reduction in health-related quality of life [ 10 ], and some women with VLS may continue to experience sexual dysfunction and less-satisfying sexual activity, even with treatment [ 12 ].…”
Section: Introductionmentioning
confidence: 99%